The Yield Curve, Inflation Expectations, and Economic Uncertainty - In-bong Kang (Korea Development Institute (KDI), 2001)
Not only individual interest rates but spreads between long-term and short-term interest rates experienced large fluctuations during the period covering several months before and after the recent foreign exchange crisis. In June 1997 the market yields on 3- year corporate bonds and 3-month commercial papers were 11.65% and 12.05%, respectively, and the spread between them (i.e. the 3-year corporate bond yield minus the 3-month commercial paper yield; henceforth CCP) was just - 40 basis points. Six months later the 3-year and 3-month rates jumped up to 24.31% and 29.26%, respectively, with the spread enlarging to - 495 basis points. During the same period the yields on the 3- year and 1-year industrial finance debentures (IFD) that were issued by the governmentowned Korea Development Bank also fluctuated large: from 12.08% and 12.25%, respectively, in June 1997 to 22.41% and 20.02% in January 1998 and then down to 6.90% and 6.92% in June 1999. So did the long-short spread between them (henceforth FF): from -17 basis points to +239 basis points to - 2 basis points. The present paper makes an attempt to understand what factors are responsible for causing such large fluctuations in long-short interest rate spreads. It develops an empirical model of the term structure of interest rates, based on the preferred habitat theory, where long-short spreads are related to inflation expectations (or short-term interest rates) and economic uncertainty. The model is then estimated and tested to see if the relationship is supported by data. A vector autoregression (VAR) model is also used to examine how long-short spreads respond to innovations to the two factors and which of the two factors is more important in explaining the forecast error variance of long-short spreads. The sample period under study is January 1991 - September 2000 and the frequency of the data is monthly.
Keywords: 330